-3(4x-1)-3=-2(9x+11)-2

Simple and best practice solution for -3(4x-1)-3=-2(9x+11)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4x-1)-3=-2(9x+11)-2 equation:


Simplifying
-3(4x + -1) + -3 = -2(9x + 11) + -2

Reorder the terms:
-3(-1 + 4x) + -3 = -2(9x + 11) + -2
(-1 * -3 + 4x * -3) + -3 = -2(9x + 11) + -2
(3 + -12x) + -3 = -2(9x + 11) + -2

Reorder the terms:
3 + -3 + -12x = -2(9x + 11) + -2

Combine like terms: 3 + -3 = 0
0 + -12x = -2(9x + 11) + -2
-12x = -2(9x + 11) + -2

Reorder the terms:
-12x = -2(11 + 9x) + -2
-12x = (11 * -2 + 9x * -2) + -2
-12x = (-22 + -18x) + -2

Reorder the terms:
-12x = -22 + -2 + -18x

Combine like terms: -22 + -2 = -24
-12x = -24 + -18x

Solving
-12x = -24 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
-12x + 18x = -24 + -18x + 18x

Combine like terms: -12x + 18x = 6x
6x = -24 + -18x + 18x

Combine like terms: -18x + 18x = 0
6x = -24 + 0
6x = -24

Divide each side by '6'.
x = -4

Simplifying
x = -4

See similar equations:

| 1/4(x-3/8)=1/8 | | 3(2x+5)=2(3x-4) | | 1d/4=-2/4 | | -7+5y=-16 | | 3(3x-6)-18=-3(5x+5)-4 | | -9=-3y-7x | | -8x-y=-6 | | 0.3x+3.8=x | | 33.8-32= | | -9x+3y=9 | | -7x+5=-16 | | 1/9c+36=7/9c+5 | | -2+x/3=5 | | -30=5a | | 6(7b-7)=-4+4b | | y=0.8x+3 | | 2/3(12-3h)=h | | 7d+4d-6d+2-8=2d | | 3y=-4x+12 | | -7(1+2x)=23-8x | | -3(3x-6)-18=-3(5s+5)-4 | | -4(1+7m)=30+6m | | n=250/100(2) | | 4(k-9)+18=6 | | -8a^2-6a+9=0 | | -y+2=0 | | 4n+4/2=-13 | | y=0.9x+3 | | 1.92+.04x=1.92+.08x | | 2x+6/x+3 | | 25X+6-27X=5-9 | | 3(z-2)=2(z+7) |

Equations solver categories